Analysis of Delay Factors Leading to Contract Disputes in Construction Projects: A Case Study of Badung Regency - I Putu Kresna Suputra Kresna; I Gede Fery Surya Tapa; I Ketut Sutapa (Jurnal Ilmiah Telsinas, 2026)
In every construction project implementation, what is often a source of problems and disputes is project delays where debates about who and what are the causes and also demands between the owner and the implementer. This study aims to identify the factors causing delays that have the potential to cause disputes. The method used is descriptive statistical analysis. After obtaining the factors causing delays that have the potential to cause disputes, the second stage questionnaire was distributed again to see the level of agreement of each cause of project delays that have the potential to cause disputes. The results of this study found 53 variables that were successfully identified as causes of construction project delays that have the potential to cause disputes. For the results of the factor analysis, it was found that the most dominant factor causing construction project delays that have the potential to cause disputes was the coordination, control and evaluation of work. The coordination, control and evaluation of work factors had the largest percentage variance value among the other formed factors, amounting to 49.914%.